Research on Writing Strategies and Creative Methods in Traditional Literary Works - Yuhong Hao, Yu Feng, Xue Wu (Forest Chemicals Review)
Traditional literature means that traditional writers pay attention to the world from a unique traditional perspective and create literary works with tradition as the protagonist. It starts from the premise of historical development and the theory of literary aesthetic value. The article reviews the development track of traditional Chinese literature in the 70 years since the founding of the People’s Republic of China, conducts a moral analysis of traditional literature, and summarizes its unique artistic creation characteristics. And literary history. It differentiates and analyzes the relationship between traditional literary creation and the atmosphere of the times, social conditions, and mainstream cultural theoretical resources in order to grasp and sort out the overall morality of contemporary, traditional literary creation.